Ribosomes, membranes and organelles during meiosis in angiosperms. - Dickinson, H; Heslop-Harrison, J (1977)
Evidence is presented from both observational and analytical techniques indicating profound changes to take place in the ribosome population during male and female meiosis in some flowering plants. During microsporogenesis these appear to involve the elimination of the major part of the ribosome complement early in the meiotic prophase, and its subsequent restoration by the disintegration in the tetrad cytoplasm of 'nucleoloids', themselves synthesized in the nucleus during late prophase. In female tissue the process is essentially similar except for differences in the restoration of the ribosome population. Immediately before the eradication of the ribosomes in both sexes, a sizeable proportion of the meiocyte cytoplasm is encapsulated by double, or multiple unit membrane profiles. Significantly this cytoplasm remains unaffected by the agents responsible for the degredation of the ribosome population. These events are also reflected in the organelle populations where cycles of dedifferentiation and redifferentiation take place. In view of evidence from other organisms, it is considered unlikely that these cycles are in any way a prerequisite of meiosis, but more a characteristic of cells undergoing major changes of phase, where a cytoplasmic 'clean-up' is required before the next stage of growth may begin.